PSYCHOLOGICAL PROBLEMS FACED BY THE YEAR â ELEVEN STUDENTS OF MA NUHAD DEMAK IN SPEAKING ENGLISH - Jannah, MarÃ¢Â€Â™atul; Fitriati, Sri Wuli (English Education Journal, 2016)
Speaking English for most Indonesian students is very challenging in terms of bravery to speak the language. Most of them show anxieties when they use it to communicate with others. The aim of this research was to: 1) to explain the psychological problems faced by the year - eleven students in speaking English; 2) to explain the causes of psychological problems faced by the year - eleven students in speaking English; and 3) to explain the effects of psychological problems. A qualitative case study was used in this research. The findings were derived from classroom observation, field notes, questionnaires, and interviews. The findings revealed three results. First, the psychological problems faced by the year-eleven students in MA NurulIttihadDemak in speaking English were: 1) most of the students were afraid of making mistakes because they were afraid if they cannot convey the message clearly and being ridiculed by their friends; 2) most of them were shy because they felt that they did not have good pronunciation and they were also ashamed if their friends laugh off their wrong pronunciation; 3) most of them were anxious because when they spoke English, all of their friendsâ eyes looked at them and gave full attention to them, including their teacher. Consequently, although they had had an idea to be expressed in English, suddenly they lost their idea and they cannot say anything in front of their friends. Most of the students lacked of confidence because they felt that their English was bad and they realized that their interlocutors do not understand them or they do not understand other speakers. They lacked of motivation because they did not like English; English was boring for them; and speaking English was difficult for them. The last, psychological problems had significant effects. They inhibited the students in speaking English. They also made the speaking activity to be passive and the speaking teaching and learning process could not run well. Therefore, teachers must give a great attention to the fact that psychological problems exist in students and students must be aware of the importance of speaking skill.